Laser system for laser cladding with powder jet having particles of hard material
By using laser beam and powder jet design at specific wavelengths in laser metal deposition technology, combined with hard material particles and multi-layer systems, the problems of workpiece quality and welding speed are solved, achieving more efficient material deposition and better workpieces performance.
Patent Information
- Application Number
- CN202380037212.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-29
- Filing Date
- 2023-05-02
- Publication Date
- 2024-12-13
AI Technical Summary
The existing laser metal deposition technology has problems such as insufficient material properties and welding speed limitations in improving workpiece quality, especially when dealing with temperature-sensitive materials, it is difficult to achieve efficient material deposition.
Using laser beams with wavelengths ranging from 0.4 μm to 1.5 μm, combined with the interaction zone design of powder jet and laser beam, the laser beam is used to increase the intensity of the laser beam in the edge area to achieve more uniform heating of powder particles using hard material particles such as carbonization to prevent alloy formation and reduce residual stress, and to improve wear resistance and ductility of the workpiece through multi-layer systems and buffer layers.
It improves the material properties and welding quality of the workpiece, increases the welding speed, reduces the brittleness and deformation of the workpiece, reduces the after-treatment workload, and improves the durability of the wear protective layer.
Smart Images

Figure CN119136936A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laser system and method for laser cladding. Background Art
[0002] Laser cladding technology is used in the fields of repair, coating and joining technology, for example. It can be divided into conventional technologies (laser metal deposition (LMD), direct metal deposition (DMD) or direct energy deposition (DED)) and so-called high-speed laser metal deposition (HS-LMD or ultra-high-speed laser metal deposition (EHLA)).
[0003] like Figure 1a As shown schematically, in conventional laser metal deposition, a weld pool 16 is produced on the surface 12 of a workpiece 10 by means of a laser beam 30. A powdery filler material 20 is introduced into the weld pool 16 by means of an inert conveying gas or carrier gas through a powder nozzle arranged coaxially with the laser beam 30 or transversely with respect to the laser beam. Before impinging on the weld pool 16, the powder particles 20 or at least some of the powder particles 20 are laser-loaded in an interaction zone 40 with the laser beam 30. In the LMD method, the energy input into the workpiece 10 by means of the laser beam 30 is generally greater than the energy input into the powder particles 20. Therefore, the powder particles 20 generally melt only after impinging on the weld pool 16. If the melt solidifies, a consolidated layer is formed that is joined by melt metallurgy. The coaxial powder nozzle arrangement produces a focused powder gas jet. In order to produce a defect-free layer, the interaction time with the powder particles 20 in the weld pool 16 must in principle be long enough for a temperature equilibrium to occur between the particles 20 and the melt 16 and for the particles 20 to be transformed into a liquid state. This limits the speed of the LMD process.The large amount of laser radiation impinging on the workpiece causes large mixing and the creation of a heat affected zone 14 (WEZ).
[0004] Compared with the conventional LMD process, in the case of HS-LMD (see Figure 1b), the powdered filler material 20 is intentionally heated to a temperature in the vicinity of the melting point or to a higher temperature than the workpiece surface 12. Since the interaction zone 40 between the laser beam 30 and the powder gas jet is sufficiently large, the powder 20 is heated to such an extent that it forms a solid, in particular a molten metallurgical connection with the workpiece 10 substantially directly on the workpiece surface 12, which is also preheated by the laser beam 10. Since no time needs to be spent in melting the particles 20 in the weld pool 16, this allows a much higher feed rate of up to 500 m / min than is the case with conventional laser metal deposition (0.5 m / min to 2 m / min). The reduced energy input into the workpiece 10 leads to a significant reduction in the heat-affected zone 14 and the weld pool 16. Temperature-sensitive materials such as aluminum and casting alloys can also be coated by means of HS-LMD. HS-LMD is used for the coating of certain rotationally symmetrical components, such as brake discs or plain bearings. For material deposition by means of HS-LMD, the component is rotated and the processing head for supplying the laser beam and powder is moved, in particular, on a straight line perpendicular to the component or parallel to the axis of rotation of the component. In this way, a helical or spiral weld seam can be produced which forms a coated surface at the end.
[0005] The HS-LMD method is described, for example, in DE 10 2011 100 456 B4 or in DE 10 2018 130 798 A1. Summary of the invention
[0006] Based on the known prior art, the object of the present invention is to provide an improved laser system for laser cladding (or laser metal deposition) and an improved method for laser metal deposition. In particular, the goal is to improve the quality, in particular the material properties, of workpieces processed by means of laser metal deposition.
[0007] This object is achieved by a laser system, a method and a component having the features of the independent claims. Advantageous developments are apparent from the dependent claims, the description and the drawings.
[0008] Accordingly, a laser system for laser metal deposition is proposed, which has a laser source for generating a laser beam with a wavelength in the range between 0.4 μm and 1.5 μm. A disk laser or a fiber laser can be used as the laser source. A diode laser can also be used. In this way, for example, a laser beam with a wavelength of about 450 nm, about 515 nm, between about 800 nm and about 1000 nm, or about 1030 nm, 1060 nm or 1070 nm can be generated. The laser beam can be designed in such a way that it can be guided to the processing head by means of an optical fiber. For example, in the case of limited brightness of a diode emitter or a bar or stack, the laser beam can be satisfactorily coupled into relatively large ring and core parts of a multi-clad optical fiber due to the large available optical fiber diameter, as described in more detail below. The laser source can have a laser power between 2 kW and 24 kW. If the workpiece is a brake disk, the laser power can in particular be between 8 kW and 24 kW. If the workpiece is a sliding bearing, the laser power can in particular be 2 kW.
[0009] The laser system also has a jet nozzle for directing the laser beam to the workpiece surface and for directing a powder jet including a powdered material to the laser beam and the workpiece surface. The laser beam can be directed orthogonally to the material surface. The powder jet is tilted relative to the laser beam so as to select an interaction zone between the powder jet and the laser beam above the material surface. Such an interaction zone allows for more efficient deposition.
[0010] The laser beam emitted from the jet nozzle has a reduced intensity in the core area compared to the edge area. For example, the intensity of the central part can be less than 90% of the intensity of the edge part. Therefore, at least in the interaction zone, the intensity of the laser beam in the edge area is higher than the intensity of the laser beam in the core area, so that the powdered material is subjected to the higher intensity of the edge area when it enters the interaction zone. Due to the inclined direction of at least one powder jet relative to the laser beam, the interaction part with the laser beam varies over the cross section of the powder jet. Due to the reduced intensity in the core area, the individual powder particles are supplied with substantially uniform energy in the case of a varying interaction part. In other words, the intensity maximum of the laser beam in the edge area causes a more uniform flux distribution for each powder particle and therefore causes an expansion of the processing window to achieve a higher laser power together with a more stable welding quality. For the intensity distribution of the laser beam in the focal plane, it can be applied: I 边缘 ≥I 中心 ≥0.
[0011] The powdered material comprises hard material particles, in particular carbides, which do not dissolve after interaction with the laser beam in the interaction zone. The powder size of the hard material particles may be between 15 μm and 63 μm, in particular in the range between 15 μm and 45 μm or between 20 μm and 53 μm. The hard material particles may comprise one or more of the following materials:
[0012]
[0013] The hard material particles have the effect that they do not overheat and therefore do not dissolve when a substrate, such as an iron substrate of the matrix material, is heated. This prevents the hard material particles from alloying with the substrate in the weld pool. In other words, the hard material particles have the effect that they form a material joint connection with the weld pool generated by the laser beam on the surface of the material without dissolving, such as melting. Since the intensity is reduced in the central part of the laser beam, the hard material particles do not alloy with the material or the matrix, which means that there are fewer dissolved chemical elements. As a result, the applied layer is more durable and cracks, in particular vertical cracks, rarely occur even under stress. As a result, the ductility of the workpiece is increased and the brittleness of the workpiece is reduced. In addition, mechanical forces can be compensated by plastic deformation.
[0014] The hard material particles also have the effect of preventing or at least reducing the occurrence of residual stresses during the cooling phase of the weld pool, i.e. during the phase from the melt to the solid phase. In particular, the use of hard material particles can reduce residual stresses by 25%. As a result, deformations of the workpiece are reduced during the cooling phase. Workpieces with less deformation are more durable and, even under stress, are less prone to cracks, in particular vertical cracks. In addition, since less material has to be removed, deformations are reduced, which reduces the amount of work required for post-processing of the workpiece.
[0015] The use of hard material particles thus benefits the material properties of the workpiece processed by means of laser metal deposition. For example, due to the reduced intensity in the central part of the laser beam, 95% of the powder particles originally present in the powdered material are actually captured as hard material particles in the processed workpiece.
[0016] The workpiece can be a metal workpiece. The powdered material can include a metal material in particular. The powdered material can be radiated onto the workpiece surface by means of a carrier gas, in particular argon or helium, and / or by means of an inert gas mixture as a processing shielding gas. The processing shielding gas can additionally protect the processing position from the influence of the surrounding atmosphere. The focus of the laser beam can be located on the workpiece surface, or can be located directly above the workpiece surface. The jet nozzle can have a central opening for a laser beam with reduced intensity in the central part and an annular opening for the powdered material. The annular opening can be designed in the form of an annular gap nozzle, or in the form of a multi-jet nozzle by means of a plurality of nozzles arranged annularly around the central opening. A wide jet nozzle for generating a line powder focus can also be used. Here, the powder can be radiated to the processing position at an angle from the front and / or at an angle from the rear relative to the feed direction, for example. The diameter of the powder focus can be, for example, between 0.2 mm and about 6 mm. The workpiece can be, for example, a brake disc, a hydraulic cylinder, a pressure roller, a sliding bearing or other rotationally symmetrical workpiece.
[0017] Furthermore, a method for laser metal deposition is proposed. The method involves the step of directing a laser beam having a wavelength in a range between 0.4 μm and 1.5 μm to a workpiece surface. The method further involves the step of directing a powder jet comprising a powdered material to the laser beam and the workpiece surface. The laser beam can be directed orthogonally to the material surface. The powder jet is tilted relative to the laser beam so as to select an interaction zone between the powder jet and the laser beam above the material surface. Such an interaction zone allows for more efficient deposition. The laser beam and the powder jet are directed by means of a jet nozzle. The method involves the step of heating the powdered material in an interaction zone with the laser beam above the workpiece surface. The method further involves the step of applying the heated powdered material to the workpiece surface along a predetermined contour, in particular by means of welding, to form a wear protection layer. The wear protection layer is formed after cooling and is particularly advantageous for reducing fine dust contamination on the brake disc. Within the interaction zone, the laser beam has a reduced intensity in the core region compared to the edge region. Furthermore, the powdered material comprises hard material particles that are also present in the wear protection layer. The embodiments, effects and advantages disclosed in conjunction with the device apply accordingly to the method.
[0018] In addition, a component is proposed, in particular a brake disc, a hydraulic cylinder, a pressure roller, a sliding bearing or other workpiece, in particular a rotationally symmetrical workpiece. The component has a base body made of a substrate, in particular a casting alloy or cast iron. The base body can be produced by means of a forming process, such as casting. In addition, before the base body is subjected to laser metal deposition, the base body may have been post-processed, such as turning or milling. The component has a wear protection layer applied to the base body by means of laser metal deposition, the wear protection layer having a plurality of hard material particles according to the present disclosure. In particular, the wear protection layer is applied to the base body using a method according to the present disclosure. The wear protection layer can be designed as a two-phase or multi-phase layer system. The hard material particles are embedded in the matrix material. The hard material particles are preferably substantially spherical and each have a mixing zone with the matrix material in the edge region. The thickness of the mixing zone does not exceed 10 μm. As described above, due to the more uniform energy introduction compared to the prior art, the reduced intensity of the central part of the laser beam enables such a narrow and uniform mixing zone between the hard material particles and the matrix material above the entire wear protection layer.
[0019] In one embodiment, the component is a brake disc, wherein the wear protection layer is applied in the braking area adapted for frictional contact with a brake shoe. Due to the high strength of the hard material particles, such a brake disc exhibits low material wear when the brake disc is in frictional contact with the brake shoe. This can reduce the degree of fine dust contamination during braking.
[0020] The wear protection layer may have a thickness that varies along the surface of the substrate, wherein the outer thickness of the wear protection layer, i.e. the thickness at the outer edge portion of the component, has a different degree than the inner thickness of the wear protection layer, i.e. the thickness facing the inside of the component. Thickness refers to a dimension orthogonal to the surface of the component. In the case of a brake disc, the thickness is orthogonal to the friction surface. For example, the outer thickness of the wear protection layer may be less than the inner thickness of the wear protection layer. The wear protection layer of an adjacent component may have a plurality of hard material particles embedded in the matrix material. The features and effects according to the present disclosure may be combined with the component. The thickness variation may be caused by a post-processing step after laser metal deposition. For example, high heat input into the component during laser metal deposition may cause deformation of the component. The deformation may be more pronounced in the outer region of the component than in the inner region. Partial removal of the wear protection layer compensates for the deformation. This may cause the outer thickness of the wear protection layer to be less than the inner thickness of the wear protection layer. In one embodiment, the thickness difference between the inner thickness and the outer thickness may not exceed 200 μm, in particular 100 μm, and further in particular not exceed 50 μm. In percentage, the thickness difference relative to the minimum thickness may not exceed 40%, in particular 25%, further in particular not exceed 10%. Such small thickness differences may be caused by the combination of a laser beam with reduced intensity in the center part and hard material particles according to the present disclosure. They reduce the post-processing time required for the component and are beneficial to the material properties.
[0021] Furthermore, the component can have a buffer layer beneath the wear protection layer in order to achieve a two-layer system.
[0022] In one embodiment, the hard material particles of the powdered material include at least one material from the following group: tungsten carbide, titanium carbide, niobium-based alloys and / or chromium carbide. Tests and experiments have shown that these materials do not overheat when using a laser beam and are therefore particularly suitable for increasing ductility, reducing deformation and preventing crack formation.
[0023] In one embodiment, in addition to the hard material particles, the powdered material also has a fusible matrix material, so that a multiphase layer is formed on the workpiece surface from the powdered material, or in terms of a method step, so that a multiphase layer is applied to the workpiece surface. In the multiphase layer, the hard material particles interact with the matrix material in such a way that the multiphase has higher-quality material properties. This supports the reduction of brittleness and helps to reduce residual stresses during the cooling phase.
[0024] In one embodiment, the content of hard material particles in the powdered material is 15 to 40 volume percent, in particular 23 to 30 volume percent. For example, the remainder can be matrix material. These volume ratios represent an optimal compromise in order to achieve increased wear resistance and effective bonding by laser metal deposition.
[0025] In one embodiment, the powdered material comprises at least one material from the following group: (i) stainless steel, in particular 430L and 316L; (ii) nickel alloys, in particular corrosion-resistant nickel-based alloys; and (iii) alloys or aggregates or powder mixtures, which contain at least one of the components titanium, titanium carbide, niobium, niobium carbide, molybdenum, chromium and / or chromium carbide. These materials can be used in any combination with respect to single-layer and double-layer systems and single-phase and multi-phase layer systems. In a single-layer system, a layer of powdered material is applied to the workpiece. In a double-layer system, two layers of powdered material are applied to the workpiece, wherein the two layers are different from each other. For example, the first layer can be used as a buffer layer and the second layer can be used as a wear protection layer. In a single-phase layer system, the layer has one phase, in particular unmelted hard material particles, while in a multi-phase layer system, the layer is divided into a matrix and hard material particles.
[0026] In one embodiment, the outer diameter of the core region in the interaction zone is less than or equal to one third, particularly one quarter, further particularly one fifth, one eighth or one tenth of the outer diameter of the edge region. In other words, the outer diameter of the annular beam can be at most 10 times larger, particularly at most 5 times larger, 4 times larger or 3 times larger than the diameter of the central portion beam at at least one position. For example, the limits of the individual beam portions can be determined by means of the second-order moment method. In principle, the narrower edge region causes a more uniform temperature distribution between the powder particles due to the reduced difference in interaction time with the laser beam. The outer diameter of the laser beam, in particular the outer diameter of the annular beam according to the above-mentioned variant, can be at least 500 μm, preferably at least 1000 μm, and even more preferably at least 2000 μm at at least one position in the interaction zone. By expanding the diameter of the laser beam in the interaction zone, in particular on the workpiece surface, productivity can be increased.
[0027] In order to produce a beam distribution of a laser beam having a core region and an edge region, a multi-clad optical fiber, in particular a 2-in-1 transmission optical fiber, can be used to allow efficient beam forming. The intensity components of the core region and the annular region of the laser beam can be controllable. For example, a 2-in-1 optical fiber with a core diameter between 200 μm and 300 μm and an outer ring diameter between 700 μm and 1000 μm can be used. For example, a multi-clad optical fiber with more than one secondary core portion can also be used to produce beam distributions with different intensities in different annular regions. Additionally or alternatively, a beam shaping element, in particular a diffractive optical element (DOE) or a multi-lens array can also be used to produce the described beam distribution. In this way, a non-rotationally symmetric beam distribution, such as a linear beam distribution, can also be produced. In addition, a single-core optical fiber can also be used to produce an annular beam distribution in this way.
[0028] In one embodiment, the method involves the following steps: applying a buffer material to the workpiece surface along a predetermined contour, in particular by means of welding, to form a buffer layer on the workpiece surface, wherein the buffer material is applied before the powdered material, so that the buffer layer is formed below the wear protection layer. In this way, a two-layer system is achieved, which leads to an increased wear resistance of the workpiece.
[0029] In one embodiment, the method involves the steps of partially grinding the applied powdered material to compensate for any deformation that occurs during application. The workpiece may be a brake disc. Due to thermal stresses, deformations may occur during the cooling phase after application of the powdered material. Changes in geometrical components due to this deformation may be compensated by partial grinding.
[0030] According to the present disclosure, the laser beam in the interaction zone can have a beam distribution with a substantially annular intensity maximum. Thus, the beam distribution of the laser beam has an edge region surrounding a core region in the middle of the laser beam, wherein the laser beam preferably has a higher intensity at each point than in the core region. The edge region can also have a plurality of annular regions, the intensity of the laser beam in the interaction zone being higher in at least one annular region than in the core region. At the transition between regions, the intensity distribution can have both a gradual form and a continuous form. The intensity of the laser beam can be substantially constant along the annular shape. Alternatively, the intensity of the laser beam can be variable along the annular shape and can fluctuate, for example, by up to about 30%.
[0031] Furthermore, according to the present disclosure, the laser beam in the interaction zone can have a linear beam profile aligned substantially transversely to the feed direction of the laser beam, the linear beam profile having a front intensity maximum in the feed direction and / or a rear intensity maximum in the feed direction. The feed direction describes the direction in which the laser beam moves relative to the workpiece surface. It can include a relatively fast, in particular rotational feed rate of the workpiece and a relatively slow lateral feed rate of the processing head guiding the laser beam, so as to produce a spiral or helical material application on the workpiece surface. In the case of a laser beam with a linear beam profile, the front intensity maximum and the rear intensity maximum each extend substantially linearly transversely to the feed direction and are separated from each other by linear regions of equally low intensity (core regions of the laser beam). According to this variant, the powdered filler material can be directed obliquely from the front and / or obliquely from the rear to the processing position by means of one or more wide jet nozzles, which are aligned substantially parallel to the linear laser focus. The laser beam can also include several individual laser beams that at least partially overlap in the focal plane.
[0032] According to the present disclosure, the intensity distribution of the laser beam may be substantially flat-topped at one point. The flat-topped shape may also be referred to as a top hat. A flat-topped or top hat-shaped intensity distribution describes a sudden rise in the intensity of the laser beam at an edge portion to an intensity maximum, which is substantially maintained over the entire width of the edge region before the intensity suddenly drops again in the direction toward the core region of the laser beam. Compared to a Gaussian intensity distribution, a flat-topped or top hat-shaped intensity distribution in the edge region of the laser beam promotes a reduction in the roughness of the applied material layer. At at least one position within the interaction zone, the intensity in the core region of the laser beam may not exceed 90%, preferably not exceed 50%, and even more preferably not exceed 10% of the intensity maximum in the edge region of the laser beam. An intensity distribution with a lower intensity in the core region of the laser beam makes it possible to expand the processing window with respect to the variability of the laser power used. In particular, because more laser power is used to preheat and / or melt the powder used to coat the workpiece, the intensity distribution described in the focal plane allows the use of laser powers of >4kW while maintaining welding quality. At at least one location within the interaction zone, the power in the core region of the laser beam can be, for example, between 7% and 9% of the laser power of the entire laser beam. In the core region, the power can also be between 5% and 7%, in particular about 6%, of the total power of the laser beam. According to an alternative variant, the power in the core region can be reduced to a minimum value, that is to say in particular to 0% of the total laser power. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The preferred further embodiments of the present invention are described in more detail by the following description of the accompanying drawings. In the accompanying drawings:
[0034] Figure 1a , Figure 1b Schematic diagrams of the LMD process and the HS-LMD process are shown;
[0035] Figure 2a to Figure 2d A schematic diagram showing different laser beams and the resulting interaction of the powdered material with the corresponding laser beam;
[0036] Figure 3 shows the width of the processing window according to the beam profile of the laser beam relative to the laser power;
[0037] Figure 4a A beam profile with a ring-shaped intensity maximum is shown in cross section;
[0038] Figure 4b A linear beam profile with a front intensity maximum and a rear intensity maximum is shown;
[0039] Figure 5a to Figure 5c A workpiece to which a two-layer system is applied is shown;
[0040] Figure 6 shows the deformation of the cooled workpiece compared to conventional solutions; and
[0041] Figure 7 A schematic cross section of a brake disc is shown. DETAILED DESCRIPTION
[0042] Preferred exemplary embodiments are described below with reference to the accompanying drawings. In this case, in different figures, identical, similar or elements having the same effect are provided with identical reference numerals, and repeated description of these elements is omitted in some instances to avoid redundancy.
[0043] Described previously Figure 1a and Figure 1b The following will refer to Figure 2a to Figure 2d The influence of the intensity distribution of the laser beam on the interaction with the powdered filler material during laser metal deposition is described in more detail. Figure 2a to Figure 2d Schematically shown is a cross-sectional front view of a workpiece 10 which is locally melted for the purpose of laser metal deposition by means of a laser beam 30, thereby producing a weld pool 16 on the workpiece surface 12. When the laser beam 30 is moved perpendicularly to the plane of the figure over the workpiece 10, a filler material in the form of a powder jet 20 is radiated to the treatment point by means of a preferably inert carrier gas. For simplicity, Figure 2a to Figure 2d The application of powder from one side is shown in each case only. However, it should be understood that in the case of laser metal deposition, the filling material can be directed to the processing point in the form of a plurality of individual beams arranged in an annular manner around the laser beam or in the form of an annular beam and, in the case of a linear beam profile of the laser beam, for example in the form of a linear powder jet directed to the processing point from the front and / or from the rear. Depending on the position of the powder particles within the powder jet 20, the interaction portion of the relevant powder particles within the interaction zone 40 along which they are subjected to laser radiation has different lengths. Accordingly, depending on the trajectory of the powder particles, they are heated to different degrees by the laser beam 30. For example, while powder particles in the center of the powder jet 20 are melted in the interaction zone 40, at the same time, powder particles in the edge region of the powder jet 20 may be evaporated due to a longer or shorter interaction time with the laser beam 30 (see Figure 2a to Figure 2d powder particles on the right or at the top) or in a solid state impacting the workpiece surface 12 (see Figure 2a to Figure 2d If the laser beam 30 has a Gaussian intensity distribution 32a in the interaction zone 40, the temperature gradient of the powder particles during laser metal deposition is particularly large. Figure 2aThis is shown in . The powder particles at the outer (or bottom) edge section of the powder jet 20 are heated particularly weakly. Inconsistent interaction times of the powder particles with the laser beam 30 can have a negative impact on the welding result. With process parameters that are precisely matched to one another, high-quality welds can be ensured within a narrow process window. Changes in the laser power can already cause sensitive quality fluctuations in the welding result. Figure 2b It is shown that an improved temperature gradient of the powder particles and / or a narrower temperature bandwidth can be achieved if a laser beam 30 with a flat-top and / or top-hat-shaped intensity distribution 32 b is used.
[0044] In addition, if the interaction zone 40 has a Figure 2c or Figure 2d A laser beam 30 with intensity distributions 32c, 32d can improve the uniformity of powder heating. Figure 2c A laser beam 30 is shown with a concave intensity distribution 32c in the interaction zone 40, in which case the intensity decreases from an annular maximum towards the core region of the laser beam 30. Due to the high intensity in the edge region of the laser beam 30, powder particles with a short interaction time are still heated relatively intensively. A particularly uniform temperature distribution of the powder particles can be achieved with a coaxial powder supply with an annular intensity distribution of the laser beam 30, in which case most of the laser energy is present in the edge region of the laser beam 30. In this case, a flat-topped and / or top-hat-shaped intensity distribution 32d is found in the annular outer region of the laser beam 30 (see Figure 2d Using a laser beam 30 with such an intensity distribution can advantageously influence process stability, particularly in the case of high-speed laser metal deposition. Figure 2c and Figure 2d Each relates to a variation in which the laser beam 30 has a rotationally symmetrical cross section. It should be understood that Figure 2c and Figure 2d The illustration in can be applied analogously to a laser beam 30 with a linear beam profile, wherein the corresponding intensity distributions 32c, 32d are present only transversely to the length of the linear beam profile.
[0045] Figure 3 The variation of the process window in the case of high-speed laser metal deposition as a function of the beam profile of the laser beam used is shown by way of example. In the vertical direction the laser power in kW is plotted with which, given otherwise identical process parameters, a process can be carried out without significant losses in the quality of the welding result. The illustration relates to high-speed laser metal deposition on a tubular workpiece made of construction steel, with an outer diameter of the laser beam in the focal plane of 2000 μm and a feed rate of approximately 80 m / min. When using a laser with a Gaussian beam profile (see Figure 2a), i.e. a laser beam with a Gaussian intensity distribution of the laser beam in the focal plane, acceptable welding results can only be achieved in a very narrow power range of 4 kW to about 4.6 kW. The process window 52 is therefore very small.
[0046] In the case of a top-hat intensity distribution over its entire cross section in the interaction region (see Figure 2b ), the process window 54 is already quite large. For this process, laser powers between 4 kW and 8 kW can be used without significant losses in the quality of the welding result. The process windows 56a to 56d each relate to the use of a laser beam with an annular beam profile having a top-hat-shaped intensity profile in the annular edge region of the laser beam and having different laser powers in the core region of the laser beam. In the case of a central portion power of 9% of the overall laser power, the process window 56a corresponds essentially to a laser beam with a power according to Figure 2b 54 with a top-hat shaped intensity distribution as shown in the figure. With a relative reduction of the laser power in the core area of the laser beam to 6% of the total power, the laser power can be increased to 9 kW while maintaining good welding quality. This corresponds to a 25% enlargement of the processing window 56b compared to the processing window 54 with a top-hat shaped intensity distribution without an annular power or intensity distribution. When the power in the central part is further reduced to 3% of the total power of the laser beam, a loss in the degree of energy efficiency of the method can be identified. This means that good welding results can only be achieved with laser powers above approximately 4.6 kW. However, when using a normal laser beam with a top-hat beam distribution, the laser power that can be utilized with the processing window 56c is 10% higher than the laser power that can be utilized with the processing window 54. According to Figure 3 , the largest possible processing window 56d can be achieved with an annular beam profile, wherein all the laser power is present in the annular portion, i.e. the laser power in the central beam portion is reduced to zero (see also Figure 2d ). With this beam profile, high quality welding results can be achieved between 4.6 kW and 10 kW. This corresponds to a 35% enlargement of the process window compared to the process window 54 when using a conventional top hat beam profile. Figure 3 The comparison shows that in the case of high-speed laser metal deposition, the process window can be opened up to higher laser powers when using a laser beam with annular intensity maximum and coaxial supply of powdered filling material in the beam focus. Figure 3The findings can be transferred analogously to a laser beam with a line focus which has corresponding linear intensity maxima in the interaction zone at its front and rear edge sections in the feed direction, wherein powdery filling material is directed onto the processing point only from the front and from the rear in a linear powder jet oriented in each case essentially transversely to the feed direction.
[0047] Figure 4a and Figure 4b Different beam profiles 31a, 31b of a laser beam 30 are shown, each having a core region 314 and an edge region 312a, 312b, 312c. According to the invention, the beam profiles 31a, 31b shown can be located in a projection plane extending transversely to the propagation direction of the laser beam 30 and located in the interaction zone 40 (see FIGS. 1 and 2 ). Figure 4a The laser beam 30 has a circular intensity maximum in its annular edge region 312a and a core region 314 with an intensity lower than that of the edge region 312 (see also Figure 2d ). Figure 4b A linear beam profile 31b of the laser beam 30 is shown which is aligned transversely to the feed direction 60. Figure 4b The laser beam 30 has a front intensity maximum in its front edge region 312b and a rear intensity maximum in its rear edge region 312c in the feed direction 60. The core region 314 of the laser beam 30 is arranged between the linear intensity maxima and is likewise linear.
[0048] Figure 5a to Figure 5c Each shows a cross section of a workpiece portion to which the method for laser metal deposition is applied. The original powdered material 20 is applied to the substrate 70 of the workpiece. This is achieved by heating the powdered material with the laser beam 30, as described above, so as to form a material-bonded connection with the substrate 70, and then letting it cool. The substrate 70 can be cast iron or a cast alloy. Figure 5a to Figure 5c Workpiece sections with different layer thicknesses are shown, each section realizing a two-layer system: Figure 5a In the embodiment of the present invention, a buffer layer 80 is first applied to a substrate 70 as a first layer. By way of example, the thickness of this layer is 90 μm. A wear protection layer 90 is applied on top of the buffer layer 80 as a second layer. This layer contains hard material particles 100. Figure 5a In the exemplary embodiment shown in FIG. 1 , the thickness of the wear protection layer 90 is 170 μm. Since the wear protection layer 90 with the hard material particles 100 is applied to the substrate 70 and there is a buffer layer 80 between the wear protection layer and the substrate, the material properties of the workpiece are improved compared to the case where the hard material particles 100 are directly applied to the substrate 70. Figure 5bCompared to the embodiment in FIG. 1 , improved wear resistance can be achieved by adding the wear protection layer 90. Figure 5b In the exemplary embodiment shown in FIG. 8 , the thickness of the buffer layer 80 is also 90 μm. The thickness of the wear protection layer 90 arranged on top is 130 μm. Figure 5a Compared to the embodiment in FIG. 1 , a higher feed rate can be achieved due to the reduction of the wear protection layer 90. Figure 5a , Figure 5b In the exemplary embodiment shown in FIG. 1 , a laser source with an output power of 8 kW is used by way of example, which enables a feed rate of 145 m / min. The diameter of the hard material particles 100 is between 15 μm and 63 μm, in particular between 15 μm and 45 μm or between 20 μm and 53 μm. The hard material particles 100 are embedded in the matrix material. A mixing zone exists between the hard material particles 100 and the matrix material. Figure 5a , Figure 5b In the embodiment of the present invention, the mixed zone can be identified as a dark edge around the hard material particles 100. The mixed zone is small compared to the diameter of the essentially spherical hard material particles 100. For each hard material particle 100, the thickness of the mixed zone does not exceed 10 μm, in particular does not exceed 8 μm, 6 μm, 4 μm or 2 μm.
[0049] Figure 5c A further two-layer system is shown. A buffer layer 80 is applied to the substrate 70, to which a wear protection layer 90 is applied with a thickness in the range of approximately 190 μm to 245 μm. The wear protection layer 90 contains hard material particles 100. Figure 5c In the exemplary embodiment shown in , a laser source with an output power of 10.5 kW is used by way of example. By way of example, the hard material particles 100 are formed from tungsten carbide. Alternatively, the materials disclosed at the outset are also conceivable. Figure 5a to Figure 5c In the double-layer system, there are no cracks: there are no identifiable inclusions between the individual hard material particles 100 or at other locations. This increases the ductility of the workpiece and reduces the brittleness. For example, due to the reduced intensity in the central part of the laser beam, 95% of the powder particles originally present in the powdered material 20 are actually captured as hard material particles in the processed workpiece.
[0050] The use of hard material particles 100 has the effect that they do not overheat and therefore do not dissolve when the substrate 70 is heated. Thus, the hard material particles 100 are prevented from alloying with the substrate 70 or creating air inclusions which would increase residual stress in the substrate 70. Residual stress causes deformation due to the shielding effect when the workpiece cools. Figure 6The deformation in the case of laser metal deposition according to the present disclosure and conventional laser metal deposition is compared. The use of hard material particles 100 reduces the residual stresses that occur. As a result, the deformation of the workpiece during cooling is reduced by, for example, 24%. This improves the quality of the workpiece and reduces the amount of material to be removed after deformation, which is beneficial for material utilization.
[0051] Figure 7 A cross section of a rotationally symmetrical component, in particular a brake disc, is shown after a wear protection layer 90 has been applied by means of laser metal deposition and after grinding has been performed. The inner thickness d1 of the wear protection layer 90 is greater than the outer thickness d2. This means that more material is removed from the inner region of the wear protection layer 90 than from the outer region, which had essentially the same thickness as the inner region before grinding. The reason for this phenomenon is that the shielding effect of the outer region of the component causes a greater deformation than the inner region. The brake disc is a rotationally symmetrical component. The inner region is therefore the radially inner region and the outer region is the radially outer region. The reduced center part strength in combination with the hard material particles means that the difference between the radially inner thickness d1 and the radially outer thickness d2 does not exceed 200 μm, in particular not more than 100 μm, further in particular not more than 50 μm. Expressed as a percentage, the thickness difference relative to the minimum thickness must not exceed 40%, in particular 25%, further in particular not more than 10%.
[0052] To the extent applicable, all the individual features presented in the exemplary embodiments may be combined with one another and / or interchanged without departing from the scope of the present invention.
Claims
1. A laser system for laser metal deposition, comprising: - a laser source for generating a laser beam (30) having a wavelength in the range between 0.4 μm and 1.5 μm; as well as a jet nozzle for directing the laser beam (30) to the workpiece surface (12) and for directing a powder jet comprising powdered material (20) to the laser beam (30) and to the workpiece surface (12); wherein the laser beam (30) emitted from the jet nozzle has a reduced intensity in a core region (314) compared to an edge region (312a, 312b, 312c); and Wherein, the powdery material (20) comprises hard material particles (100).
2. The laser system according to claim 1, wherein: The hard material particles (100) of the powdery material (20) include at least one material from the following group: tungsten carbide, titanium carbide, a niobium-based alloy and / or chromium carbide.
3. The laser system according to claim 1, wherein: In addition to the hard material particles (100), the powdered material (20) also comprises a meltable matrix material, so that a multiphase layer is formed on the workpiece surface (12) from the powdered material (20).
4. The laser system according to claim 1, wherein: The hard material particles (100) account for 15 to 40 volume percent, in particular 23 to 30 volume percent, of the powdery material (20).
5. The laser system according to claim 1, wherein: The powdered material (20) comprises at least one material from the following group: -Stainless steel; - Nickel alloys, especially corrosion-resistant nickel-based alloys; - an alloy or an aggregate or a powder mixture comprising at least one of the components titanium, titanium carbide, niobium, niobium carbide, molybdenum, chromium and / or chromium carbide.
6. The laser system according to claim 1, wherein: The outer diameter of the core region (314) is less than or equal to one third, in particular one quarter, and further in particular one eighth of the outer diameter of the edge region (312a, 312b, 312c).
7. A method for laser metal deposition comprising the following steps: - directing a laser beam (30) having a wavelength in the range between 0.4 μm and 1.5 μm onto the workpiece surface (12); - directing a powder jet comprising powdered material (20) towards the laser beam (30) and the workpiece surface (12); - heating the powdery material (20) in an interaction zone (40) with the laser beam (30) at least partially above the workpiece surface (12); - applying, in particular cladding, a heated powdered material (20) to the workpiece surface (12) along a predetermined contour to form a wear protection layer (90); wherein within the interaction zone (40) the laser beam (30) has a reduced intensity in a core region (314) compared to an edge region (312a, 312b, 312c); and Therein, the powdery material (20) comprises hard material particles (100) which are also present in the wear protection layer (90).
8. The method according to claim 7, wherein: The hard material particles (100) of the powdery material (20) include at least one material from the following group: tungsten carbide, titanium carbide, a niobium-based alloy and / or chromium carbide.
9. The method according to claim 7 or 8, wherein: In addition to the hard material particles (100), the powdered material (20) also comprises a meltable matrix material, so that a multiphase layer is applied to the workpiece surface (12).
10. The method according to any one of claims 7 to 9, wherein: The hard material particles (100) account for 15 to 40 volume percent, in particular 23 to 30 volume percent, of the powdery material (20).
11. The method according to any one of claims 7 to 10, wherein: The powdered material (20) comprises at least one material from the following group: -Stainless steel; - Nickel alloys; - an alloy or an aggregate or a powder mixture comprising at least one of the components titanium, titanium carbide, niobium, niobium carbide, molybdenum, chromium and / or chromium carbide.
12. The method according to any one of claims 7 to 11, wherein: The outer diameter of the core region (314) is less than or equal to one third, in particular one quarter, and further in particular one eighth of the outer diameter of the edge region (312a, 312b, 312c).
13. The method according to any one of claims 7 to 12, comprising the steps of: - applying, in particular cladding, a buffer material to the workpiece surface (12) along a predetermined contour to form a buffer layer (80) on the workpiece surface (12); The application of the buffer material is performed before the application of the powdery material (20) in terms of time, so that the buffer layer (80) is formed below the wear protection layer (90).
14. The method according to any one of claims 7 to 13, comprising the steps of: - Partial grinding of the applied powdered material in order to compensate for deformations occurring during said application.
15. A component comprising: A base body, which is made of a base material (70), in particular a casting alloy or cast iron; as well as A wear protection layer (90) which is applied to the base body and comprises a plurality of hard material particles (100) embedded in a matrix material; wherein the wear protection layer (90) is applied in particular by means of a method according to claims 7 to 14; wherein The hard material particles (100) each have a mixed zone with the matrix material in the edge region with a thickness of at most 10 μm.
16. The component according to claim 15, wherein The component is a brake disc, wherein the wear protection layer (90) is applied in a braking area adapted for frictional contact with a brake shoe.
17. A component according to any one of claims 15 or 16, wherein The wear protection layer (90) has a varying thickness along the surface of the substrate, wherein an outer thickness (d2) of the wear protection layer (90) is different from an inner thickness (d2) of the wear protection layer (90).
18. The component according to claim 17, wherein The thickness difference between the inner thickness (d1) and the outer thickness (d2) is at most 200 μm, in particular at most 100 μm, and even more in particular at most 50 μm.
19. The method according to any one of claims 15 to 18, wherein: A buffer layer (80) without hard material particles (100) is arranged below the wear protection layer (90).
Citation Information
Cited By
Device for testing thermal erosion resistance of blade
CN121856085A
